2016
DOI: 10.1097/md.0000000000005234
|View full text |Cite
|
Sign up to set email alerts
|

Change of ascending reticular activating system with recovery from vegetative state to minimally conscious state in a stroke patient

Abstract: Rationale:We report on a stroke patient who showed change of the ascending reticular activating system (ARAS) concurrent with recovery from a vegetative state (VS) to a minimally conscious state (MCS), which was demonstrated on diffusion tensor tractography (DTT).Patient concerns:A 59-year-old male patient underwent CT-guided stereotactic drainage 3 times for management of intracerebral hemorrhage and intraventricular hemorrhage.Diagnosis:After 4 months from onset, when starting rehabilitation, the patient sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
29
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(31 citation statements)
references
References 16 publications
2
29
0
Order By: Relevance
“…In this patient, we could not analyze the lower ARAS between the pontine reticular formation and the intralaminar thalamic nucleus or the right parietal portion of the upper ARAS due to artifacts related to the VP shunt. We suggest that the large lesions observed in the left cerebral cortex and subcortical white matter were the major cause of impaired consciousness in this patient [6][7][8][9]20]. In addition, the right prefrontal injury due to subfalcine herniation may have contributed to impaired consciousness in this patient [21].…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…In this patient, we could not analyze the lower ARAS between the pontine reticular formation and the intralaminar thalamic nucleus or the right parietal portion of the upper ARAS due to artifacts related to the VP shunt. We suggest that the large lesions observed in the left cerebral cortex and subcortical white matter were the major cause of impaired consciousness in this patient [6][7][8][9]20]. In addition, the right prefrontal injury due to subfalcine herniation may have contributed to impaired consciousness in this patient [21].…”
Section: Discussionmentioning
confidence: 69%
“…The introduction of diffusion tensor tractography (DTT), which is derived from diffusion tensor imaging (DTI) data, enables three-dimensional evaluation of the ARAS in a live human brain [1][2][3][4]. As a result, many studies have used DTT to show improvements in impaired consciousness concurrent with ARAS injury recovery in patients with disorder of consciousness (DOC) [5][6][7][8][9]. It has been widely reported that repetitive transcranial magnetic stimulation (rTMS) has a therapeutic effect on impaired consciousness in patients with DOC [10][11][12]; however, little has been reported on the direct effect of rTMS on the ARAS.…”
Section: Introductionmentioning
confidence: 99%
“…Differences in CFFF without changes in psychometric tests could be explained by CFFF interrogating much lesser complex physiological pathways than psychometric tests (Hemelryck et al, 2013). Arousal is triggered by the stimulation of the ascending reticular substance (Jang et al, 2016) and it could be interrogated by CFFF. Furthermore, the decrease in CFFF could be due to decreased cerebral blood flow index Some similar results have been reported during acute orthostatic stimulations altering cerebral blood flow (Balestra et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…187 Diffuse lesions are predominant in TBI, 216 so the imaging of specific tracts is less promising, although it was performed successfully. 9,143,146,149, 150,190,218,236,264,287 In retrospective, patients with TBI could be identified by DTI analyses, 8 which once more underlines the technique as a promising possible biomarker for white matter injury. A significant number of articles studied white matter injury with DTI measurements such as FA or average tract length.…”
Section: Tractography In the Treatment Of Tbi And Spontaneous Intracrmentioning
confidence: 99%